Report of the seminar on engineering and traffic aspects of highway safety - Seminar on Engineering and Traffic Aspects of Highway Safety (13-23 May, 1975 : Tokyo); United Nations. Economic Commission for Asia and the Far East (Bangkok : United Nations, 1958)
08